Long-term recolonization patterns of ants in Western Australian rehabilitated bauxite mines, with reference to use as indicators of restoration success - Majer, Jonathan; Nichols, O. (1998)
1. The return of invertebrate animals to rehabilitated mine pits is desirable for the re-establishment of ecosystem functioning. A long-term ant monitoring programme is reported over 14 years in a jarrah Eucalyptus marginata forest control plot and in three bauxite mine pits, one of which had been left unvegetated, one planted with marri trees E. calophylla and the other seeded with mixed native plant species.2. The results confirm published findings for the first 2 years of the succession that seeding with mixed species results in a more rapid attainment of a forest-like ant fauna, although in the last 6 years of the study the ant fauna of the planted plot had become more similar to that of the seeded plot.3. Changes in the nature of the ant fauna are described and it is concluded that although composition has substantially converged on that of the forest by the end of the study, differences still persist.4. Research on vegetation, spiders and ants in bauxite mined areas which have been rehabilitated using more recent technology suggest that these differences will lessen with time and with the introduction of improved rehabilitation prescriptions.5. An additional aim of the study was to validate the chronosequence approach to studying ecosystem recovery following disturbances such as mining. It is concluded that long-term studies provide important information that is missed by the chronosequence approach. Ideally, rapid-feedback chronosequence approaches should be augmented by long-term case studies.